2016
DOI: 10.3892/or.2016.4684
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin inhibits cell proliferation and induces apoptosis through G2/M phase cell cycle arrest in hepatocellular carcinoma stem cells

Abstract: The present study was designed to investigate the effect of cantharidin on cell proliferation, ability of selfrenewal, cell cycle arrest and induction of apoptosis in HepG2 hepatocellular carcinoma stem cells (HCSCs). It was observed that cantharidin treatment exhibited dose- and time-dependent inhibitory effect on the viability of HCSCs. The inhibition of cell viability by cantharidin in HepG2 CD133+ and parental cells was significant at the concentration 5 and 15 µM, respectively after 48 h. Cantharidin trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Apoptosis is a procedure of programmed cell death involving caspases occurring in cells as inactive proenzymes . Previous studies have shown that cantharidin induced apoptosis through blocks the cell cycle, and this effect is mediated by cell cycle arrest at the G2/M phase . CA is a phosphatase inhibitor and thus induces cytochrome c release and elevated activation of caspase‐3 in the pancreatic beta cell line HIT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is a procedure of programmed cell death involving caspases occurring in cells as inactive proenzymes . Previous studies have shown that cantharidin induced apoptosis through blocks the cell cycle, and this effect is mediated by cell cycle arrest at the G2/M phase . CA is a phosphatase inhibitor and thus induces cytochrome c release and elevated activation of caspase‐3 in the pancreatic beta cell line HIT .…”
Section: Discussionmentioning
confidence: 99%
“…in HCC stem cells. 17 Moreover, numerous studies have shown NCTD, a cantharidin analog, exhibits anticancer activities, including apoptosis, antiproliferative activity, and antimetastatic activity in the HCC cell lines. [18][19][20][21] Our previous study also showed that, compared with the IC50 (21 lM) of cantharidin, anhydride-modified cantharidin analogs exhibited low cytotoxicity (IC50 > 200 lM) in primary cultured rat hepatocytes.…”
mentioning
confidence: 99%
“…In the current study, our data showed a decrease in the proportion of CNE-2 cells at the G2/M phase of the cell cycle in the transfection group relative to the blank and negative control groups 24 h post-exposure to X-ray radiation, suggesting the relief of the cell cycle arrest at the G2/M phase, and the reduction in the proportion of CNE-2 cells at the G2/M phase resulted in relative radiation resistance in CNE-2 cells overexpressing β-catenin. Inhibition of β-catenin expression was found to significantly increase the proportion of hepatocellular carcinoma stem cells in the G2/M phase [45], and treatment with polyphyllin I (PPI), a major active constituent extracted from Paris polyphyllin, caused down-regulation of β-catenin expression in multiple myeloma cells and cell cycle arrest at G2/M phase [46]. These findings demonstrate the close correlation between β-catenin and cell cycle.…”
Section: Discussionmentioning
confidence: 58%
“…Following radiation-induced DNA damages, DNA damage-related genes trigger the mechanism of cell-cycle regulation, and allow the cell cycle arrest at G1/S and G2/M checkpoints, resulting in cell cycle arrest at G1 and G2 phases [44]. Since the G1/S checkpoint is deficient in most types of cancer cells, the G2/M checkpoint arrest is a major determinant governing the radiation sensitivity in cancer cells [45]. In the cell cycle, cells in the G2/M phase are most sensitive to radiation, and a reduction in the proportion of cells at the G2/M phase indicates the insensitivity to radiation [44].…”
Section: Discussionmentioning
confidence: 99%
“…PP2A targets many oncogenic signaling cascades and was initially characterized as a tumor suppressor (12), however, accumulating evidence points to its anti-apoptotic role in multiple cancer cell types (12), as well as a contribution to chemotherapy resistance mechanisms (13). Pharmaceutical inhibitors of PP2A compromise cancer cell proliferation, survival and invasion (12, 14, 15) and are considered promising for treatment of particular types of cancer (12, 13). In our study, NF1-deficient MEFs as well as all NF1-associated MPNST cells were significantly more sensitive to Cantharidin compared to wild type MEFs, suggesting that pre-malignant and malignant NF1-associated tumor cells biology depends on PP2A activity.…”
Section: Discussionmentioning
confidence: 99%